Determinan Harga Saham Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Aureal Meilani Karsono; Astuning Saharsini (Akuntansi, 2024)
The research of this study was to determine the effect of CR, EPS, DER, ROE and ROA on the share price of the banking sector. This research used secondary data in the form of financial statements. There are 47 banking sector companies listed on the IDX in 2019-2022 as a population by sampling using purposive sampling method so that a sample of 15 companies is obtained. This study uses the classical assumption test method, multiple linear regression analysis, and hypothesis testing. The results of the research conducted show that simultaneously all independent variables have an influence on stock prices. Partially, EPS has an effect on stock prices. CR, DER, ROE and ROA have no effect on stock prices.